STRATEGI BAURAN PEMASARAN 4 P USAHA KECIL MENENGAH (UKM) Studi Kasus Perusahaan Furnitur Kayon Living - , Saskia Prisandhini, Dr. lin Maya Sari, M.M., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
was Kayon Living established on 2009 and expected to become a trendsetter furniture design furniture and accessories with a domicile in Jakarta. Kayon Livingproducts were made from mahogany furniture, leather, rattan and brass. Its selling price is considered affordable for the Jakarta middle class, Rp 1- 6 million per furniture. Its main business model is to sell self-produced furniture products, while also serving the interior design and furniture design according client's wishes, and the contractor to build low-rise buildings in Jakarta. Kayon Living is a growing Small and Medium Enterprise. This research aimed to understand marketing strategies that can accommodate major business model Kayon Living, which is selling its furniture products to its ideal market segmentation. Based on research, marketing mix aspects of Kayon Living were performed by order of the creative process of product design, then determining the price concept, its promotion, making brochures and exhibitions. The promotion process lasts for 6 months since product launched. After that, there will be discount period. were created by mixing customer input and Kayon Living Products combining itto the analysis of market trends and desires of Director. Selection of the Place is adjusted to be closer to potential customers. Kayon Living is currently running using the passive promotion, relying on others, which in this case word-of-mouth promotion by customers and exhibition invitationsby the Ministry of Small and Medium Enterprises. The concept of price is adjusted to the price of manufacturing goods with a certain profit margin calculations. ies Currently, succession of Kayon Living Marketing Plan rel heavily on third parties. This situation is based on minimum promotion budget. The research explores how Kayon Living optimalise its sales force and extensive customer relation, and right market orientation to better Marketing Mix with limited capital budget, considering enterprise's nature asgrowing Small and Medium Enterprise.